2021
DOI: 10.2147/ppa.s311601
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking Preferences to Informal and Formal Source of Care for Depression: A Community-Based Study in Northwest Ethiopia

Abstract: Background: Globally, 350 million people are suffering from depression. Many people suffering from depression use different sources of help for their problems. People with different mental health problems seek help from formal and/or informal sources. This gives crucial information on community beliefs and perception regarding their preference for help. This study helps to guide effective planning and provision of mental health services, and health policy of the country to explore the community's preference to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
0
14
1
Order By: Relevance
“…One possible explanation is that they are easier to access. In addition, they are usually reliable sources of support, especially emotional and informational support, and may help patients with MDD to seek help from healthcare settings ( 14 ). Relying on these helps to reduce stigmatization is another explanation ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation is that they are easier to access. In addition, they are usually reliable sources of support, especially emotional and informational support, and may help patients with MDD to seek help from healthcare settings ( 14 ). Relying on these helps to reduce stigmatization is another explanation ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…A patient’s perceived helpfulness of treatment is an important issue, evidenced by the results of the World Mental Health Surveys (WMHS), which showed that 68.2% patients with MDD considered the treatment helpful ( 13 ). Moreover, in fact, most residents were more likely to seek help from some non-healthcare sources (such as intimate partner, parents, friends) for depression ( 14 ). In China, a previous study provided 23 potential sources for patients with mental disorder to receive help ( 15 ) and also showed that Chinese patients with mental disorders were likely to seek different kinds of help-seeking sources and their first-choice helps were sought in non-healthcare sources.…”
Section: Introductionmentioning
confidence: 99%
“…People prefer to seek help from less formal sources such as the family for mental health problems [ 48 ]. Studies have shown that the most common source of help for people about health treatment is talking to family or friends [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies [ 35 37 ] have explored the feasibility of online help-seeking via the internet. These possibilities call for an evaluation on the comparative effectiveness of various help-seeking behaviors across informal/formal sources [ 38 , 39 ] and offline/online channels [ 40 , 41 ]. In view of this, the third objective of this study was to compare the transition pattern in suicidal ideation among individuals with different help-seeking behaviors.…”
Section: Introductionmentioning
confidence: 99%